1994
DOI: 10.2307/2410473
|View full text |Cite
|
Sign up to set email alerts
|

Global Survey of Mitochondrial DNA Sequences in the Threespine Stickleback: Evidence for Recent Migrations

Abstract: Phylogenetic analyses of mitochondrial DNA (mtDNA) sequences were used to assess the matriarchal genetic structure of the threespine stickleback, Gasterosteus aculeatus. A 747 base-pair (bp) fragment of the cytochrome b was sequenced from 36 individuals collected from 25 localities in Europe, North America, and Japan. Two major divergent clades were revealed: one widespread in Japan but with representatives in some Alaskan and British Columbian lakes and the other common in Europe and North America. A simple d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
193
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(212 citation statements)
references
References 57 publications
17
193
2
Order By: Relevance
“…Previous studies show that phylogenies of freshwater stickleback populations in British Columbia based on putatively neutral markers are well approximated by a star phylogeny (e.g. [27]). …”
Section: Materials and Methods (A) Samplingmentioning
confidence: 99%
“…Previous studies show that phylogenies of freshwater stickleback populations in British Columbia based on putatively neutral markers are well approximated by a star phylogeny (e.g. [27]). …”
Section: Materials and Methods (A) Samplingmentioning
confidence: 99%
“…First, the G. aculeatus species complex includes both anadromous and freshwaterresident forms of G. aculeatus (Bell and Foster 1994;McKinnon and Rundle 2002). The ancestral forms of G. aculeatus are considered anadromous, whereas freshwater-resident forms have evolved independently from the anadromous forms in multiple lineages (Haglund et al 1992;Orti et al 1994;McPhail 1999, 2000;McKinnon et al 2004;Colosimo et al 2005). The anadromous forms of G. aculeatus usually migrate to freshwater or estuaries in spring (Table 1), while juveniles migrate to the sea in fall (Table 2), although there are substantial variation in the timing of migration (Tables 1, 2).…”
Section: Diversity Of Migration In Gasterosteus Aculeatusmentioning
confidence: 99%
“…(b) Comparisons with genetic breaks found in other species Our ¢ndings of a distinct genetic break without apparent phenotypic di¡erentiation in common ravens is similar to cryptic genetic variation documented in many other taxa (reviewed in Avise 2000). However, few previous studies have shown such a deep mitochondrial split that is geographically structured but has such a wide contact zone (but see Orti et al 1994, sticklebacks; R. C. Fleischer, unpublished data, Asian elephants). For example, Carolina chickadee haplotypes completely shift from one mitochondrial type to the other across a relatively narrow 400 km east^west transect (Gill et al 1993(Gill et al , 1999; also see Patton & da Silva 1998).…”
Section: K E Omland and Others Cryptic Genetic Variation And Paraphmentioning
confidence: 99%